Penerapan Algoritma C4.5 Untuk Prediksi Kualitas Pelayanan Terhadap Kepuasan Konsumen (Studi Kasus: Hinet Batam) - Sherly Maisa Putri; Sasa Ani Arnomo (Journal of Information System Research (JOSH), 2020)
Quality of service is the goal of the company in providing satisfaction to consumers both service and non-service companies. One of the internet access service provider companies that is committed to improving service quality to customer satisfaction is Hinet Batam. This study aims to analyze the quality of service to Hinet Batam consumer satisfaction using the C4.5 algorithm. Valuation variables include empathy, responsiveness, reliability with satisfied and dissatisfied decisions. The results of processing the Data Mining method using the C4.5 algorithm were able to classify the level of customer satisfaction with service quality. With a satisfied predictive precision value of 61.7% and an unsatisfied predictive precision value of 38.3%. The results of this study can be used as a reference to improve service quality and to maintain customer loyalty in using internet service data package products and increase sales.